Investigations of couette flow unsteady radiative convective heat transfer in a vertical channel using the generalized method of lines (MOL) - Sowayan, Ahmed S. (Zielona Góra: Uniwersytet Zielonogórski)
This study describes a very efficient and fast numerical solution method for the non-steady free convection ?ow with radiation of a viscous ?uid between two in?nite vertical parallel walls. The method of lines (MOL) is used together with the Runge-Kutta ODE Matlab solver to investigate this problem numerically.
Keywords: vertical channel; radiation; natural convection; Method of lines (MOL); Runge-Kutta method; Matlab ODE solvers